Pengaturan Batasan Nominal Uang Pengganti Kerugian dalam Penyelesaian Perkara Pidana dengan Pendekatan Keadilan Restoratif dalam Perspektif Kepastian Hukum (Pusat Riset dan Inovasi Nasional, 2026)
This study examines the urgency of regulating the nominal limit of restitution in criminal case resolution through a restorative justice approach from the perspective of legal certainty. Restorative justice in Indonesia is governed by PERKAP No. 8 of 2021, PERJA No. 15 of 2020, and PERMA No. 1 of 2024. However, none of these regulations explicitly stipulate the nominal limit of compensation payable to victims. The absence of such a provision potentially leads to legal uncertainty and unfair practices, particularly in cases where resolution depends on the offender's ability to pay restitution. This research adopts a normative juridical method using statutory and conceptual approaches. The study aims to analyze the necessity of regulating nominal limits and how such limits should be determined under the prevailing legal framework. The findings reveal that the lack of clear restitution limits hampers the effective implementation of restorative justice, undermines fairness, and fails to adequately protect victims' rights. Legal regulation of compensation limits is necessary to ensure legal certainty, prevent abuse of power, and uphold justice in the victim recovery process. The study recommends that the state promptly establish clear restitution limits through revision of existing regulations or formulation of new ones, taking into account the principles of justice, the offender’s financial capacity, and the proportionality of the victim's losses.